Ponderings II-VI : black notebooks 1931-1938 - Heidegger, Martin, 1889-1976 (Studies in Continental thought., 2016)
Ponderings II'VI begins the much-anticipated English translation of Martin Heidegger's "Black Notebooks." In a series of small notebooks with black covers, Heidegger confided sundry personal observations and ideas over the course of 40 years. The five notebooks in this volume were written between 1931 and 1938 and thus chronicle Heidegger's year as Rector of the University of Freiburg during the Nazi era. Published in German as volume 94 of the Complete Works, these challenging and fascinating journal entries shed light on Heidegger's philosophical development regarding his central question of what it means to be, but also on his relation to National Socialism and the revolutionary atmosphere of the 1930s in Germany. Readers previously familiar only with excerpts taken out of context may now determine for themselves whether the controversy and censure the "Black Notebooks" have received are deserved or not. This faithful translation by Richard Rojcewicz opens the texts in a way that captures their philosophical and political content while disentangling Heidegger's notoriously difficult language.